Modificaciones de la estructura ósea del fémur proximal : Análisis de una muestra esqueletal - Plischuk, Marcos (2014)
Purpose: Analyses of osteoporosis in human bone remains become relevant because allow us to evaluate the health of past population. An usual area used for estimating the loss of bone mineral density is the proximal epiphysis of the femur. The aim of this paper is to analyze changes in proximal femoral bone structure, in relation to body mass, sex and age of individuals. Materials and methods: The sample consist of 30 left femurs belonging to Prof. Dr. R. Lambre Osteological Collection, housed at the Faculty of Medical Sciences, National University of La Plata. Two indices were estimated radiologically (Trabecular Index and Cortico Metaphyseal Index), and related to body mass, sex and age of individuals. Results: The average value estimated by Cortico Metaphyseal Index pointed to a low quality of bone, with no differences between males and females. This index showed no correlation with age and weight of individuals. A 50% of the individuals showed a Trabecular Index indicative of osteoporosis, with no significant difference between sexes. Conclusion: The poor quality of the bone material observed was adjusted to expectation, given the age of the individuals analyzed, which conspired against the visibility of other processes causing the loss of Bone Mineral Density happened earlier in the life of individuals.